Autosomal STRs provide genetic evidence for the hypothesis that Tai people originate from southern China. - Hao Sun (Public Library of Science (PLoS), 2013)
Tai people are widely distributed in Thailand, Laos and southwestern China and are a large population of Southeast Asia. Although most anthropologists and historians agree that modern Tai people are from southwestern China and northern Thailand, the place from which they historically migrated remains controversial. Three popular hypotheses have been proposed: northern origin hypothesis, southern origin hypothesis or an indigenous origin. We compared the genetic relationships between the Tai in China and their "siblings" to test different hypotheses by analyzing 10 autosomal microsatellites. The genetic data of 916 samples from 19 populations were analyzed in this survey. The autosomal STR data from 15 of the 19 populations came from our previous study (Lin et al., 2010). 194 samples from four additional populations were genotyped in this study: Han (Yunnan), Dai (Dehong), Dai (Yuxi) and Mongolian. The results of genetic distance comparisons, genetic structure analyses and admixture analyses all indicate that populations from northern origin hypothesis have large genetic distances and are clearly differentiated from the Tai. The simulation-based ABC analysis also indicates this. The posterior probability of the northern origin hypothesis is just 0.04 [95%CI: (0.01-0.06)]. Conversely, genetic relationships were very close between the Tai and populations from southern origin or an indigenous origin hypothesis. Simulation-based ABC analyses were also used to distinguish the southern origin hypothesis from the indigenous origin hypothesis. The results indicate that the posterior probability of the southern origin hypothesis [0.640, 95%CI: (0.524-0.757)] is greater than that of the indigenous origin hypothesis [0.324, 95%CI: (0.211-0.438)]. Therefore, we propose that the genetic evidence does not support the hypothesis of northern origin. Our genetic data indicate that the southern origin hypothesis has higher probability than the other two hypotheses statistically, suggesting that the Tai people most likely originated from southern China.